INKLUSI SOSIAL PELAYANAN TRANSPORTASI SUROBOYO BUS DALAM PERSPEKTIF HIMPUNAN WANITA DISABILITAS (HWDI) KOTA SURABAYA - Sibuea, Dipahot; Fitrotun Niswah; Meirinawati Meirinawati; Eva Hany Fanida (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Social inclusion of people with disabilities in Surabaya reflects the government's commitment to creating equitable and friendly governance for all citizens, without exception. As a metropolitan city with a high level of development, Surabaya has strived to provide various facilities that support the fulfillment of the rights of people with disabilities, such as guiding blocks, ramps, braille, priority seats, and other facilities. However, behind these achievements, there is still a gap between the regulations that have been made and their implementation in practice. Various field findings indicate that some people with disabilities, especially members of the Indonesian Women's Association of Disabled People (HWDI) of Surabaya City, still face obstacles. This study aims to describe the social inclusion of Suroboyo Bus transportation services in Surabaya City from the perspective of the Indonesian Women's Association of Disabled People (HWDI) of Surabaya City using the principles of social inclusion of the World Bank (2022). This study uses a qualitative method with a descriptive approach. Data collection techniques were carried out through participatory observation, in-depth interviews, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of the study indicate that social inclusion of Suroboyo Bus transportation services is still partial. Positively, the Surabaya City Transportation Agency's efforts to provide inclusive facilities are quite adequate. However, there is a gap between regulations, implementation, and the actual experiences of members of the Indonesian Association of Women with Disabilities in Surabaya. This study recommends conducting a phased infrastructure evaluation and involving organizations of persons with disabilities that actively advocate for the rights of persons with disabilities.